Arsenic Hyperaccumulation Strategies: An Overview - Souri, Zahra; Karimi, Naser; Sandalio, Luisa M. (Frontiers in Cell and Developmental Biology, 2017)
Arsenic (As) pollution, which is on the increase around the world, poses a growing threat to the environment. Phytoremediation, an important green technology, uses different strategies, including As uptake, transport, translocation, and detoxification, to remediate this metalloid. Arsenic hyperaccumulator plants have developed various strategies to accumulate and tolerate high concentrations of As. In these plants, the formation of AsIII complexes with GSH and phytochelatins and their transport into root and shoot vacuoles constitute important mechanisms for coping with As stress. The oxidative stress induced by reactive oxygen species (ROS) production is one of the principal toxic effects of As; moreover, the strong antioxidative defenses in hyperaccumulator plants could constitute an important As detoxification strategy. On the other hand, nitric oxide activates antioxidant enzyme and phytochelatins biosynthesis which enhances As stress tolerance in plants. Although several studies have focused on transcription, metabolomics, and proteomic changes in plants induced by As, the mechanisms involved in As transport, translocation, and detoxification in hyperaccumulator plants need to be studied in greater depth. This review updates recent progress made in the study of As uptake, translocation, chelation, and detoxification in As hyperaccumulator plants.